CRISPR/Cas9 Gene Editing of Gluten in Wheat to Reduce Gluten Content and Exposure—Reviewing Methods to Screen for Coeliac Safety - Jouanin, Aurelie; Gilissen, Luud J. W. J.; Schaart, Jan G.; Leigh, Fiona J.; Cockram, James; Wallington, Emma J.; Boyd, Lesley A.; van den Broeck, Hetty C.; van der Meer, Ingrid M.; America, A. H. P.; Visser, Richard Gerardus Franciscus; Smulders, Marinus J. M. (Frontiers in Nutrition, 2020)
Ingestion of gluten proteins (gliadins and glutenins) from wheat, barley and rye can cause coeliac disease (CD) in genetically predisposed individuals. The only remedy is a strict and lifelong gluten-free diet. There is a growing desire for coeliac-safe, whole-grain wheat-based products, as consumption of whole-grain foods reduces the risk of chronic diseases. However, due to the large number of gluten genes and the complexity of the wheat genome, wheat that is coeliac-safe but retains baking quality cannot be produced by conventional breeding alone. CD is triggered by immunogenic epitopes, notably those present in 𝜶-, 𝜸- and ω-gliadins. RNA interference (RNAi) silencing has been used to down-regulate gliadin families. Recently, targeted gene editing using CRISPR/Cas9 has been applied to gliadins. These methods produce offspring with silenced, deleted, and/or edited gliadins, that overall may reduce the exposure of patients to CD epitopes. Here we review methods to efficiently screen and select the lines from gliadin gene editing programs for CD epitopes at the DNA and protein level, for baking quality, and ultimately in clinical trials. The application of gene editing for the production of coeliac-safe wheat is further considered within the context of food production and in view of current national and international regulatory frameworks.